Microplastics and cadmium pollution in Chinese sweet potato fields - Shi, Liang; Xu, Yuan; Chen, Zanming; Liu, Binhao; Hou, Yanan; Li, Jianmin; Dang, Fei; Wang, Yujun; Shen, Zhenguo; Yang, Jinghui; Chen, Yahua (Frontiers in Sustainable Food Systems, 2024)
Context and background Microplastics (MPs) and heavy metals (HMs) coexist in the farmland of China. Motivation It still remains unclear the extent of their exposure and distribution in sweet potato fields. Hypothesis Polyethylene (PE) or polyamide (PA) is the main MP pollutant in contaminated sweet potato sites, and the MP abundance in low-latitude and eastern areas is highest. Methods: In this study, saturated NaCl solution, a stereo microscope, a Fourier transform infrared spectrometer, and an electrothermal digester are used for the extraction, observation, identification of MPs, and analysis of Cd elements in soil, respectively. Methods In this study, saturated NaCl solution, a stereo microscope, a Fourier transform infrared spectrometer, and an electrothermal digester are used for the extraction, observation, identification of MPs, and analysis of Cd elements in soil, respectively. Results Here, we found an average MP level of 112,400 items/kg in 30 sweet potato field sites based on the items in 5 g soil and the magnification (200x), and the maximum abundance was 197,153 items/kg in Laiyang city, Shandong province, by field survey. The distribution characteristics of MPs are middle-latitude areas < low-latitude areas, and eastern areas > central areas. Most MPs are of the fragment and film shape, which account for 47.96 and 40.22%, respectively. In order to detect MP polymers in three cities named “Liancheng,” “Huanggang,” and “Laiyang” with different degrees of development, a laser infrared imaging system was used as a novel instrument to explore the MPs larger than 10 μm. Conclusion The results showed that PA is the main MP pollutant in contaminated sweet potato sites, and soil texture, planting time, and urbanization processes may be the main factors affecting MP distribution. The average cadmium (Cd) concentration in 215 field sites is 0.15 mg/kg, and the local Cd pollution is existing, but the overall pollution is low. In addition, Cd concentration was negatively correlated with MP abundance. This study reveals the status of MP and also Cd pollution in sweet potato fields, which provides a theoretical basis for the safe production and utilization of sweet potato fields.